STRATEGIC MANAGEMENT AND EMPLOYEE ENGAGEMENT IN ORGANIZATION - Sukphon, Nonthavat (Asian Administration and Management Review, 2023)
The objectives of this study were (1) to study the elements and strategies for building employee engagement in the organization; (2) to examine the factors affecting the employee engagement in the organization; and (3) to generate the strategies for building employee engagement in the organization. This study is a mixed methods research design between quantitative and qualitative research with following research methodologies, namely, 1) Studying and synthesizing elements and strategies for building employee engagement in the organization 2) Surveying the factors affecting employee engagement in the organization, and 3) Generating strategies for building employee engagement in the organization. The results were found that (1) the elements and strategies for building employee engagement in the organization consisted of several factors, namely, HCM strategies, human management, human development, and HCM environment. (2) The HCM strategies, human management, human development, and HCM environment had impact on the employee engagement in the organization at the statistical significance level of 0.05. (3) The strategies for building employee engagement in the organization consisted of 4 strategies: strategy 1: organizational culture improvement, strategy 2: compensation and benefit management, strategy 3: upgrading proactive human resources department, and strategy 4: improvement of quality of life in safety, occupational health, and working environment, which are appropriate and consistent and can cover the elements of employee engagement, and each factor was related and can clearly explain the said elements.